Closing the Financial Privacy Loophole: Defining “Access” in the Right to Financial Privacy Act - W. F. McElroy (Washington University Law Review, 2017)
Part I of this Note will discuss the Miller decision and the hole it left in the Fourth Amendment’s protection of financial information left in the hands of trusted third parties. Part II will discuss Congress’s response to Miller in the RFPA. Part III will discuss the cramped interpretation of the RFPA affirmed by the Sixth Circuit, its misapplication of the statute, and policy problems arising from the acceptance of the court’s interpretation. Part IV will discuss statutory injuries and how the ambiguous outcome of the Spokeo case could threaten financial privacy protections generally and those specifically provided by the RFPA. Part V will discuss the proposed solution to the problem.
Keywords: Fourth Amendment; RIGHT TO FINANCIAL PRIVACY ACT; reasonable expectation of privacy; financial records; RFPA; 12 U.S.C. §§ 3401–3422; United States v. Miller; Brackfield & amp; Associates P’ship v. BB& amp; T Co.; Spokeo; Inc. v. Robins; third party doctrine